Mediating Effects of Innovation Capability on Market Orientation and Community Economic Enterprise Performance - Rachmawati, Avianita; Surya, Surya (International Journal of Multidisciplinary Research of Higher Education, 2025)
Innovation is one of the important keys in improving the competitiveness and sustainability of community economic enterprises. This study aims to analyze the mediating effect of innovation capability on market orientation and community economic business performance. This research uses a quantitative method with a survey type. Data sources were taken using a questionnaire with a total of 52 questionnaire items. Data from the questionnaire was taken from 150 respondents from a total population of 218. All data were correlation analyzed using SEM & PLS software version 3. The results showed that market orientation directly has a significant effect on innovation capability and community economic business performance. Indirectly, market orientation mediated by innovation capability has a significant influence on community economic enterprise performance. This study found that innovative capabilities and market focus have a real impact in determining the success of community economic enterprises. This finding is expected to contribute and information specifically to community economic businesses regarding the mediating role of innovation capabilities in the relationship between market orientation and community economic business performance.